Density of scots pine seedlings in pine forests under the influence of emissions from the Karabash copper smelter and forest fi res - Kuyantseva, Nadezhda Borisovna; Mumber, Aleksandr Геннадьевич; Molchanova, Darya Alexandrovna; Веселкин, Денис Васильевич (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология)
We assessed the features of natural pine regeneration in forests with diff erent ages of ground fi res in the Southern Urals depending on the level of heavy metal pollution. Using the materials obtained from 81 sample plots laid in maturing, mature and over-mature pine forests of natural origin in three types of forest growth conditions (TFGC 1 – TFGC 3), the relationship between the density of pine seedlings and the state of forest stands (crown density, stand age, vital status index), with the characteristics of vegetation condition (total number of species, total projective cover of herb-shrub layer, projective cover of bryophytes layer), with external infl uences (pollution level, distance from emission source, duration of fi re disturbance), and with the methodological features of the study (accounting year) was analyzed. The high variability of estimates of the density of pine seedlings did not allow us to identify the relationship between the density of seedlings and the level of pollution and/or fi re disturbances. The density of seedlings is nonlinearly related to the protective cover of the herb-shrub layer. With increasing coverage of the herb-shrub layer, the density of seedlings increased in areas with high levels of pollution and decreased in areas with background pollution.